The Analysis Of Honorary Teachers Motivation At SMK Negeri 1 Lamongan - Sari, Kafita Rusnaya; Pristyadi, Budiyono (Jurnal Mahasiswa Manajemen, 2020)
This study aims to identify the motivation of honorary teachers who teach and also the reason they have survived to date at SMK Negeri 1 Lamongan. This study uses a qualitative research approach with a case study method. Infoman in this research amounted to six people, the types and sources of data used included primary data. Data retrieval techniques use interviews. The data analysis technique uses 3 stages that is, data reduction, data display (data presentation), and conclusion drawing / verification. The results of this study can be concluded that the work motivation of the internal motivational honorary teacher is the desire to gain recognition. External motivation is good environmental conditions, good supervision, and flexible regulations. The reasons that make honorary teachers survive teaching for tens of years are needs, home distance factors, age factors, and also work environment factors.